2020
DOI: 10.3389/fnins.2020.00706
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Specific Risk Factors and Comorbidities of Bothersome Tinnitus

Abstract: Objective: This study aims to identify gender-specific risk factors associated with the presence of bothersome tinnitus (compared with non-bothersome tinnitus), including sociodemographic and lifestyle factors, tinnitus-associated phenomena (hearing loss, traumatic experiences, sleep disturbances), and physical as well as mental comorbidities. Methods: We conducted a cross-sectional study using survey data from the Swedish LifeGene cohort containing information on self-reported tinnitus (N = 7615). We (1) anal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 51 publications
3
32
0
2
Order By: Relevance
“…As our result show that the answers of the daily questionnaires can predict the gender of TYT users, inversely, the daily answers can be indicators for the symptom differences of men and women. As we further found out that the worst symptom is an important feature, we are in line with other research works beyond the scope of mHealth data 13 , 58 – 60 . Furthermore, studies that have found gender-related differences in tinnitus patients without using mHealth solutions might particularly benefit from the use of mHealth.…”
Section: Discussionsupporting
confidence: 91%
“…As our result show that the answers of the daily questionnaires can predict the gender of TYT users, inversely, the daily answers can be indicators for the symptom differences of men and women. As we further found out that the worst symptom is an important feature, we are in line with other research works beyond the scope of mHealth data 13 , 58 – 60 . Furthermore, studies that have found gender-related differences in tinnitus patients without using mHealth solutions might particularly benefit from the use of mHealth.…”
Section: Discussionsupporting
confidence: 91%
“…A study that examined gender-specific differences in comorbidities in individuals with tinnitus found higher rates of chronic shoulder pain and osteoarthritis in both sexes, as well as higher rate of fibromyalgia in women, for individuals with bothersome tinnitus compared to non-bothersome tinnitus [16]. We found the same tendency here-an association between chronic pain and tinnitus that was stronger when the tinnitus definition was restricted to individuals with more bothersome tinnitus.…”
Section: Plos Onesupporting
confidence: 77%
“…If the auditory and nociceptive systems are in fact connected, one might expect that tinnitus and chronic pain are associated irrespective of the severity and anatomic location of pain–that is, a more general association between the two phenomena. Still, as indicated by a study on chronic shoulder pain, osteoarthritis and fibromyalgia among tinnitus patients, the degree of tinnitus bother may affect the strength of the association [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, available evidence suggests that women tend to report higher HRQoL impairments in the context of psychological [38][39][40] or medical difficulties [41,42]. For chronic tinnitus, similar patterns emerged with women describing higher levels of emotional tension, psychological distress, and functional impairment [43][44][45][46], although these findings remain inconclusive [47,48]. To date, investigations on genderspecific differences in HRQoL for patients with chronic tinnitus are sparse.…”
Section: Introductionmentioning
confidence: 97%